Monte Carlo simulations of ceiling scatter in nuclear medicine: 99mTc, 131I and 18F. Issue 3 (17th March 2017) - Schnerr, Roald S.; de Jong, Anouk N.; Landry, Guillaume; Jeukens, Cécile R.L.P.N.; Wierts, Roel
Abstract : Purpose: In the design of nuclear medicine treatment and examination rooms, an important consideration is the shielding required for ionizing radiation from the radioactive isotopes used. The shielding in the walls is normally limited to a height lower than the actual ceiling height. The direct radiation, possibly with build‐up correction, can be calculated relatively easily. However, little data are available to estimate the dose contribution from ionizing radiation traveling over the wall shielding and scattering off the ceiling. We aim to determine the contribution of the ceiling scatter to the radiation dose outside nuclear medicine rooms. Methods: Monte Carlo simulations were performed using Gate for different heights of lead shielding in the wall, and different ceiling heights. A point source in air of 99m Tc (141 keV), 131 I (365 keV) or 18 F (511 keV) was placed 1.0 m above the floor, 3.0 m from the lead shielding. Simulations of ceiling scatter only and for the total radiation dose were performed for these 3 isotopes, 5 different ceiling heights and 4–8 different wall shielding heights, resulting in a total of 165 simulations. This allowed us to compare the contribution of the radiation passing through the shielding and the ceiling scatter. Results: We find that the shielding required for the primary radiation, measured in half‐value layers, is an important factor in determining the relative contribution of ceiling scatter. When more than about 4 half‐value layers of shielding are used, ceiling scatter becomes the dominant factor and should be taken into account in the shielding design. In many practical cases for low energy photons (e.g. from 99m Tc; 141 keV; half‐value layer of 0.26 mm lead), 2 mm of lead is used and ceiling scatter is a dominating factor contributing >~70% of the dose outside the shielded room. For higher energies (e.g. 18 F; 511 keV; half‐value layer of 3.9 mm lead) the ceiling scatter is typically less than about 15% when 8 mm of lead shielding is used. Conclusions: We have performed simulations that allow an estimation of the contribution of ceiling scatter to the radiation dose outside a room, based on the ceiling height, shielding height, and isotope used. This will allow for improved shielding designs in nuclear medicine departments.